Optimization of RNA isolation from stone fruits at different ripening stages - Pfeiffer, P.; Halász, J.; György, Z.; Pedryc, A.; Hegedűs, A. (International Journal of Horticultural Science, 2009)
This study was conducted to select the most appropriate RNA isolation method that can be used successfully in case of stone fruits. The changing pattern of gene expression during the ripening process of stone fruits may elucidate the molecular background of several phenotypical or phytochemical alterations present among different genotypes. Our laboratory aims to study the expression of genes encoding for enzymes that catalyze crucial steps in the flavonoid biosynthesis pathway. RNA isolation from fruit mesocarp is a challanging task due to high levels of sugars and polyphenolics accumulating during fruit development. Therefore, at first, the optimal techniques eligible for RNA isolation from fruit tissues at different ripening stages must be selected. Our study compares three different RNA isolation protocols and describes their potential applicability according to different fruit species and ripening stages.